Impacts of Tamarix‐mediated soil changes on restoration plant growth. Issue 3 (27th November 2012) - Lehnhoff, Erik A.; Menalled, Fabian D.
Abstract: Question: Do soils impacted by Tamarix spp. affect the growth of plants used for restoration through altered soil chemistry and/or plant‐soil feedbacks? Location: The Bighorn River, the Yellowstone River and the Fort Peck Reservoir, Montana, western USA. Methods: Soil was collected from paired subsites where Tamarix was either present or absent along three water bodies. To evaluate chemical and biological soil effects on plant growth, eight plant species ( Achnatherum hymenoides, Astragalus cicer, Dalea candida, Elymus lanceolatus, Leymus cinereus, Pascopyrum smithii, Ratibida columnifera and Trifolium pratense ) commonly used in restoration projects at Tamarix ‐invaded sites were grown in the collected soil. Plant‐soil feedbacks were evaluated by growing two species ( D. candida and P. smithii ) in greenhouse soils inoculated with small amounts of the field soils. Germination, emergence and growth characteristics were compared between Tamarix ‐invaded and un‐invaded subsites and across water bodies. Results: Seedling emergence and plant relative growth rate, total biomass production and allocation of resources to roots and shoots were not negatively affected in field soils or in greenhouse soil inoculated with soil from areas where Tamarix was present. In fact, overall, plants emerged earlier and produced more biomass in soils affected by Tamarix than in soils from where Tamarix was not present. These results indicate that for sites in the northern range of Tamarix, restoration would not be inhibited by Tamarix ‐induced soil changes. Conclusions: Tamarix is a relatively new invader in the northern USA, and little is known about its impacts in this area or the potential implications for restoration. However, our results indicate that neither altered soil chemistry nor plant‐soil feedbacks negatively impact native plant growth, and restoration efforts would not be hindered by Tamarix ‐induced changes to soil chemistry or microbiota. Abstract : Some non‐native plants can induce soil chemistry changes or biologically‐mediated plant‐soil feedbacks (PSF) that negatively affect other species. The impact of the non‐native Tamarix spp. on the growth of other plant species was evaluated for soils from three water bodies in Montana (USA). Altered soil chemistry increased plant growth, but biological PSF did not impact the growth of other species.